SISTEM AKUNTANSI PENJUALAN KRIPIK GEDEBOG (Studi Di UMKM BOHAYA Wonodadi Blitar) - Diana Elvianita; Ulfa Tia Febrina (Universitas Islam Balitar, 2016)
UMKM that exist at this time has been very rapid development even more numerous compared to large businesses. This is because the capital is very simple and not too much one can build a business with relatively low risk. The development of UMKM in Blitar, one of which is UMKM Gedebog chips. This study was done to solve the problems faced by UMKM Gedebog chips, especially in the sales accounting system. In conducting the study, the authors used a method of analysis and design methods. The method of analysis conducted by the study of literature, especially studying the books of literature relating to the accounting system of sales at the library, a survey on the current system, includes interviews with the owners of UMKM chips Gedebog and direct observation on the object of research to accumulate the results of the study followed by studying and analyze the results of the sale of the existing accounting system to find a solution the development of a better system. It can be concluded that the sales accounting system are the accounting system as simple as a system for recording sales transactions were executed manually. From the results of this study concluded that the accounting system of sales in the UMKM has been using a good accounting system, the sales department has been doing recording order goods by issuing a memorandum in 2 first sheet to the warehouse which was then matched with goods and handed over to the shipping department and then submitted to the buyer. The second sheet for the financial part that is inserted into a simple recording of the financial statements.